Radioimmunotherapy in non-Hodgkin’s lymphoma: can it change the course of the disease? (Hematology Meeting Reports, 2009)
Despite the advent of numerous new chemotherapeutic agents over the last 25 years, only limited progress in the treatment of non-Hodgkin’s lymphoma (NHL) has been made with these agents alone. In recent years, several new antibody-based treatments have demonstrated promising results in NHL suggesting tangible improvements in relapse free and overall survival. These new treatment approaches have included radioimmunotherapy (RIT) with 90Y-labeled ibritumomab tiuxetan and 131I-labeled tositumomab. RIT utilizes continuous delivery of low-dose radiation via radioactive isotopes conjugated to monoclonal antibodies that target the CD20 antigen located on most (>90%) B-cell lymphomas. Clinical trials of 90Y-ibritumomab tiuxetan and 131I-tositumomab have indicated that these agents are effective and well tolerated for adult patients with relapsed or refractory CD20+ follicular B-cell NHL, with the ability to produce superior overall and complete response rates to those achieved with existing therapies. A high proportion of patients who achieve a complete response with 90Y-ibritumomab tiuxetan or 131I-tositumomab exhibit durable remissions of several years - despite the presence of risk factors for poor response or early relapse. In addition, failure to respond to previous anti-lymphoma therapy, including rituximab, does not appear to preclude achieving a long-term response with 90Y-ibritumomab tiuxetan. RIT with 90Y-ibritumomab tiuxetan or 131I-tositumomab has also been shown to be effective in patients with follicular NHL when used as first-line therapy or following first-line, short-course chemotherapy ± rituximab regimens, but further clinical studies are needed to determine the long-term efficacy of these approaches.